Public policy and endogenous growth - Douglas, Seymour ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Examines the behaviour of endogenous growth when a 'small' economy faces stochastic terms of trade and infrastructure is financed through external debt rather than taxes.